Гребни средневекового Подонья (по материалам Саркела – Белой Вежи) - Флерова, В.Е. (Материалы по археологии, истории и этнографии Таврии, 1998)
A collection of 37 bone combs was formed during the excavations of the Don fortress of the 9th - 12th centuries. Sarkel - Belaya Vezha under supervision of M.I.Artamonov. Despite numerous earth works chronological distribution of the combs in layers corresponded to dating for different types. It testifies for rather substantial ability of stratigraphic column of the monument and accuracy in fixing material. 11 combs did not have precise stratigraphic data. Only two half-finished combs were found at the depth contradicting the dating of their types, and, obviously, were found in an unfixed pit. Two more fragments were half a century late, but that is possible for a peripheral monument.